2005
DOI: 10.1523/jneurosci.1478-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Cells Respond to Predicted Events during Classical Conditioning: Evidence for Eligibility Traces in the Reward-Learning Network

Abstract: Behavioral conditioning of cue-reward pairing results in a shift of midbrain dopamine (DA) cell activity from responding to the reward to responding to the predictive cue. However, the precise time course and mechanism underlying this shift remain unclear. Here, we report a combined single-unit recording and temporal difference (TD) modeling approach to this question. The data from recordings in conscious rats showed that DA cells retain responses to predicted reward after responses to conditioned cues have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
412
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(462 citation statements)
references
References 44 publications
46
412
4
Order By: Relevance
“…Consistent with previous reports 2, [5][6][7][8][9][10][11][12][13] , this population included many neurons (n = 19) that increased firing in response to reward. Notably, activity in the 19 dopamine neurons that responded to either cue or reward (cue/reward-responsive dopamine neurons) reflected the positive and negative reward prediction errors that are inherent in our task design, whereas activity in the remaining 14 cue-responsive neurons did not.…”
Section: Prediction Error Signaling In Cue-responsive Neuronssupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with previous reports 2, [5][6][7][8][9][10][11][12][13] , this population included many neurons (n = 19) that increased firing in response to reward. Notably, activity in the 19 dopamine neurons that responded to either cue or reward (cue/reward-responsive dopamine neurons) reflected the positive and negative reward prediction errors that are inherent in our task design, whereas activity in the remaining 14 cue-responsive neurons did not.…”
Section: Prediction Error Signaling In Cue-responsive Neuronssupporting
confidence: 85%
“…Waveforms from these neurons (Fig. 2b) were analyzed for features characteristic of dopamine neurons [12][13][14]32,33 (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…However, as noted earlier, simple TD models (but not PVLV) also predict a chaining of DA bursts "backward in time" from the reward to the stimulus onset, which has not been reliably observed empirically (Fiorillo, Tobler, & Schultz, 2005;Pan et al, 2005). However, this particular aspect of the data is still controversial (e.g., Niv, Duff, & Dayan, 2005) and also depends critically on the way that the input environment is represented.…”
Section: Application To Conditioning Datamentioning
confidence: 90%
“…For example, Pan et al (2005) recently showed how a TD( ) model with a high lambda value could reproduce the empirically observed pattern (i.e., no evidence of backward marching dopamine bursts). Furthermore, the data often show dopamine bursts at both the CS and US (Pan et al, 2005;Schultz, 2002)-this is incompatible with 1 A simpler possible implementation would be to just add the two delta values to produce a summed DA value, but this double counts the rewardrelated deltas because both the LV and PV contribute in this case. Nevertheless, because LV and PV deltas otherwise occur at different times, Equation 11 is very similar to adding the deltas; the PV system just dominates when external rewards are presented or expected.…”
Section: Application To Conditioning Datamentioning
confidence: 99%
“…As illustrated in Fig. 2, during classical conditioning, unexpected reward initially triggered an increase in phasic activity of DA neurons, which then shifted with learning to the conditioned stimulus (Ljungberg et al 1992;Mirenowicz and Schultz 1994;Pan et al 2005). When an expected reward was omitted, the activity of DA neurons paused at the precise time when the reward should have been delivered (Ljungberg et al 1992;Roesch et al 2007;Satoh et al 2003).…”
Section: Introductionmentioning
confidence: 94%